Customary Right Compensation and Forest Villages Development Programs of Mangrove Company at Bintuni Bay Papua Barat - Wahyudi Wahyudi; Max Jondudago Tokede; Zulfikar Mardiyadi; Ana Tampang; Mahmud Mahmud (Jurnal Manajemen Hutan Tropika, 2014)
Mangrove at Bintuni bay offers various services to indigenous communities from ecology, social, and economic. Mangrove also could be harvested accordingly to optimize contributions to indigenous communities welfares. This paper highlights implementation of customary right compensation (CRC), and Forest Villages Development programs (FVDP) of mangrove company at Bintuni Bay, Papua Barat. Company reports and documents related to CRC and FVDP from 1988 to June 2013 were reviewed and analyzed. Field works were conducted to examine the implementation of both programs at four villages of two districts. Sustained mangrove harvest for chipwood production in Bintuni bay for more than 25 years is the most outstanding achievement of mangrove utilization and management in Indonesia. Huge amount of expenditure have been spent out, and given to indigenous communities through the CRC and FVDP programs, respectively. These cover from economic, social, and environmental related programs, manufactured public facilities, scholarships, and others. However, the indigenous communities are remained poor, and failed of being self-sufficient community. It clearly impresses that the main goals to improve the welfare, prosperity of indigenous people are considerable failed. It is presumably that social culture systems, and subsistence agriculture practices contribute to the failing these programs. Mostly, forest communities in Papua are practicing subsistence agriculture, hunting, heavily relying on their surrounding natural resources, and spending all their cash or money instantly for consumption, not for saving, investments or even productive activities. Therefore, several program could be initiated to improve in achieving the CRC and FVDP missions, such as building capacity, providing counselors and strengthen local community governance, which could accelerate of being self-reliant community.